Retention of fatty acyl desaturase 1 (fads1) in Elopomorpha and Cyclostomata provides novel insights into the evolution of long-chain polyunsaturated fatty acid biosynthesis in vertebrates 06 Biological Sciences 0604 Genetics 06 Biological Sciences 0601 Biochemistry and Cell Biology 06 Biological Sciences 0603 Evolutionary Biology - Lopes-Marques M. (2018)
Background: Provision of long-chain polyunsaturated fatty acids (LC-PUFA) in vertebrates occurs through the diet or via endogenous production from C18 precursors through consecutive elongations and desaturations. It has been postulated that the abundance of LC-PUFA in the marine environment has remarkably modulated the gene complement and function of Fads in marine teleosts. In vertebrates two fatty acyl desaturases, namely Fads1 and Fads2, encode 5 and 6 desaturases, respectively. To fully clarify the evolutionary history of LC-PUFA biosynthesis in vertebrates, we investigated the gene repertoire and function of Fads from species placed at key evolutionary nodes. Results: We demonstrate that functional Fads1Δ5 and Fads26 arose from a tandem gene duplication in the ancestor of vertebrates, since they are present in the Arctic lamprey. Additionally, we show that a similar condition was retained in ray-finned fish such as the Senegal bichir and spotted gar, with the identification of fads1 genes in these lineages. Functional characterisation of the isolated desaturases reveals the first case of a Fads1 enzyme with 5 desaturase activity in the Teleostei lineage, the Elopomorpha. In contrast, in Osteoglossomorpha genomes, while no fads1 was identified, two separate fads2 duplicates with 6 and 5 desaturase activities respectively were uncovered. Conclusions: We conclude that, while the essential genetic components involved LC-PUFA biosynthesis evolved in the vertebrate ancestor, the full completion of the LC-PUFA biosynthesis pathway arose uniquely in gnathostomes. © 2018 The Author(s).